2013
DOI: 10.4103/0377-4929.120366
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and phenotypic expression of decorin as modulator of angiogenesis in human potentially malignant oral lesions and oral squamous cell carcinomas

Abstract: Micro vessel density and VEGF-A expression were significantly associated with reduced decorin expression in tumor stroma suggesting, decorin as angiogenic modulator in OSCC. Down-regulation of decorin expression and the presence of lymph node metastasis were adverse factor independently affecting overall survival in OSCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…To our knowledge, only one study has investigated the expression of the VEGFA gene in human oral squamous cell carcinoma . Our results indicate that aggressive oral squamous cell carcinomas exhibit high VEGFA transcript levels, and thus, VEGFA expression may be an important prognostic factor in this type of cancer.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…To our knowledge, only one study has investigated the expression of the VEGFA gene in human oral squamous cell carcinoma . Our results indicate that aggressive oral squamous cell carcinomas exhibit high VEGFA transcript levels, and thus, VEGFA expression may be an important prognostic factor in this type of cancer.…”
Section: Discussionmentioning
confidence: 76%
“…Few studies have investigated the expression of the VEGFA gene in OSCC and, to our knowledge, no study has evaluated its expression in tumor margins. In this study, we investigated the expression of the VEGFA gene and its immunohistochemical expression in oral squamous cell carcinomas (OSCC) and tumor margins.…”
Section: Introductionmentioning
confidence: 99%
“…Cawthorn and coworkers found that high decorin expression was associated with lymph node metastasis and poor clinical outcome in breast cancer; thus, decorin was proposed as an adverse prognostic and predictive biomarker [ 45 ]. Conversely, downregulation of decorin and lymph node metastasis independently predicted poor prognosis in oral squamous cell carcinomas [ 46 ]; DCN expression in osteosarcoma cells blocked their metastatic spread to the lungs [ 47 ]; and virus-mediated decorin delivery inhibited the growth of breast cancer and suppressed metastasis formation in various organs [ 48 , 49 , 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, DCN exhibits antiangiogenic activities during cutaneous wound healing, while higher DCN expression was detected in human benign tumors vs. malignant vascular tumors (Jarvelainen et al, 2006;Salomaki et al, 2008). Meanwhile, impaired angiogenesis was found in the injured cornea of DCN-null mice (Schonherr et al, 2004), and repressed angiogenesis was also present in some tumors associated with reduced DCN expression (Nayak et al, 2013;Chui et al, 2014). These studies suggest that DCN can be either stimulatory or suppressive for angiogenesis, which may be related to the physiologic and pathologic conditions of tissues (Järveläinen et al, 2015).…”
Section: Angiogenesismentioning
confidence: 99%